Analisis Semiotika Roland Barthes pada Sampul Majalah Tempo (Revolusi 4.0 adalah Kunci) edisi 12-18 November 2018 - Hukubun, Lejar Daniartana (IMAGIONARY, 2025)
Book/magazine covers are one of the important things in protecting books, apart from that, they are also useful in introducing what is in the book, to communicate to the public, so that it is more attractive, appropriate illustrations or designs are needed and represent the contents of the magazine or book. Next, it is necessary to study the meaning of connotation and denotation through Roland Barthes' semiotic theory.